Importance Of Neurolinguistics As A Science - Kurbanova Dilnoza Arslanovna (Euro Asian Journal Publishing, 2024)
It has already been proven in science that the activity of human speech is coordinated by both hemispheres of the brain. The left hemisphere is responsible for the correctness of speech, and the right hemisphere is responsible for providing images and emotional color. This article covers neurolinguistics and its importance as a science. The connection of neurolinguistics with other sciences is justified.
Keywords: Neurolinguistics; thinking; justified; linguistics